Patient acceptance of a telemedicine service for rehabilitation care: A focus group study. (May 2019) - Jansen-Kosterink, Stephanie; Dekker-van Weering, Marit; van Velsen, Lex
Abstract: Background and purpose: Despite positive outcomes, widespread implementation of telemedicine services in rehabilitation care is lacking. This could, for a large part, be attributed to a lack of end-user acceptance. The aim of this article is to look beyond the common theoretical approaches towards end-user acceptance (like the Technology Acceptance Model and the Unified Theory of Acceptance and Use of Technology), and to explore the factors that contribute to or hinder the acceptance of a telemedicine service for rehabilitation care by patients with a chronic disease. Methods: A qualitative, exploratory focus group approach was applied. We involved 188 patients in 22 focus groups. A guide was developed to provoke a discussion among participants of a rehabilitation clinic on the topic of using an online portal with a wide range of telemedicine features (e.g., an exercise module and a teleconference module). Three coders, using thematic analysis, coded the focus group transcripts simultaneously. Results: The focus groups resulted in a wide range of factors that drive or hinder patient acceptance. Facilitators included the possibility to exercise from the comfort of home, the ability to work on one's recovery, irrespective of the time schedule of care professionals, and improved quality of exercise instruction, due to the provision of exercise videos on the portal. Barriers included a lack of intrinsically motivation, experiencing portal-mediated communication with care professionals as 'impersonal', and the lack of physical space and rest to properly exercise at home. Generally speaking, participants were enthusiastic about the idea to provide the telemedicine service as a follow-up treatment as they liked to be in contact with their therapist and to continue training. Conclusion: Acceptance of telemedicine services depends on many factors that are not part of well-established theories that explain technology acceptance. These factors are more specific than general determinants, such as ease of use and usefulness, and focus mainly on contextual factors, such as a fit between the service configuration and daily life, personal motivation and the associated psychological burden.